2017
DOI: 10.1186/s12877-017-0486-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in GP decisions on antihypertensive treatment in oldest-old and frail individuals across 29 countries

Abstract: BackgroundIn oldest-old patients (>80), few trials showed efficacy of treating hypertension and they included mostly the healthiest elderly. The resulting lack of knowledge has led to inconsistent guidelines, mainly based on systolic blood pressure (SBP), cardiovascular disease (CVD) but not on frailty despite the high prevalence in oldest-old. This may lead to variation how General Practitioners (GPs) treat hypertension. Our aim was to investigate treatment variation of GPs in oldest-olds across countries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 20 publications
1
40
0
2
Order By: Relevance
“…Considering the poor financial situation for many inhabitants of Western Balkan countries ( 29 ), using such medication could greatly burden a patient’s household or reduce compliance as Selmanovic et al found in their study ( 30 ). It would be interesting to explore in what way does a physician make a decision in favor of one brand when there are no restrictions placed by funds ( 31 , 32 ). All restrictions regarding medication prescribing competency of family physicians involving certain ARB antagonists, diuretics, or beta blockers should be reexamined and adjusted to best evidence-based recommendations ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the poor financial situation for many inhabitants of Western Balkan countries ( 29 ), using such medication could greatly burden a patient’s household or reduce compliance as Selmanovic et al found in their study ( 30 ). It would be interesting to explore in what way does a physician make a decision in favor of one brand when there are no restrictions placed by funds ( 31 , 32 ). All restrictions regarding medication prescribing competency of family physicians involving certain ARB antagonists, diuretics, or beta blockers should be reexamined and adjusted to best evidence-based recommendations ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The complete survey described eight case vignettes where oldest-old male or female patients presented for a routine control (Additional file 1 in [11]). These patients had no symptoms suggesting hypertension and took no antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a re-analysis of data from the cross-sectional case-vignettes study called 'Antihypertensive TreaTmENT In Very Elderly' (ATTENTIVE) [11].…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations